2013
DOI: 10.1210/jc.2012-2710
|View full text |Cite
|
Sign up to set email alerts
|

Metformin in Obese Children and Adolescents: The MOCA Trial

Abstract: Metformin therapy has a beneficial treatment effect over placebo for BMI-SDS, fasting glucose, ALT, and ALR ratio at 3 months, with changes in BMI-SDS sustained at 6 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
86
2
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(100 citation statements)
references
References 139 publications
5
86
2
3
Order By: Relevance
“…The third study, conducted in children and adolescents (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18) years old) with the shorter-acting (1000 mg in the morning and 500 mg in the evening) formulation, reported a placebosubtracted reduction in BMI of 1.1 kg/m 2 (BMI reduction of ≈3%) over a treatment period of 6 months. 202 None of the other cardiometabolic risk factors measured in the study improved at 6 months. A meta-analysis of 5 studies (with treatment periods ≥6 months) that used metformin in children and adolescents reported a placebo-subtracted reduction in BMI of 1.42 kg/m 2 .…”
Section: Metforminmentioning
confidence: 82%
See 1 more Smart Citation
“…The third study, conducted in children and adolescents (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18) years old) with the shorter-acting (1000 mg in the morning and 500 mg in the evening) formulation, reported a placebosubtracted reduction in BMI of 1.1 kg/m 2 (BMI reduction of ≈3%) over a treatment period of 6 months. 202 None of the other cardiometabolic risk factors measured in the study improved at 6 months. A meta-analysis of 5 studies (with treatment periods ≥6 months) that used metformin in children and adolescents reported a placebo-subtracted reduction in BMI of 1.42 kg/m 2 .…”
Section: Metforminmentioning
confidence: 82%
“…Only 3 randomized controlled trials specified change in BMI as a primary efficacy end point. 189,201,202 The first study, conducted in adolescents (13-18 years old) with the extended-release formulation (2000 mg once per day), reported a placebo-subtracted reduction in BMI of 1.1 kg/m 2 (BMI reduction of ≈3%) over a treatment period of 1 year. 189 No improvements in lipid profile, blood pressure, or markers of insulin resistance were observed.…”
Section: Metforminmentioning
confidence: 99%
“…We prescribe Bofu-tsusho-san to mild obesity children and have observed consistent effects. A previous study also demonstrated that Metformin hydrochloride, an insulin sensitizer indicated for the treatment of insulin resistance in type 2 diabetes that may reduce appetite by increasing glucagon-like-peptide levels, was effective in reducing body weight (34).…”
Section: Pharmacotherapymentioning
confidence: 94%
“…Three randomized, placebo-controlled trials conducted in obese youth without diabetes mellitus reported a BMI reduction of ≈3% over a treatment period of 6 to 12 months. [226][227][228] Neither glucagon-like peptide-1 receptor agonists nor dipeptidyl peptidase-4 inhibitors are currently approved by the US Food and Drug Administration for the treatment of T2DM in children and adolescents. However, if the safety and efficacy of these drug classes are established and US Food and Drug Administration approval is obtained, these medications may be an attractive option because glucagon-like peptide-1 receptor agonists are associated with weight loss and dipeptidyl peptidase-4 inhibitors appear to be weight neutral, although safety concerns about long-term treatment exist that are based on recent autopsy studies.…”
Section: Type 2 Diabetes Mellitusmentioning
confidence: 99%